2012
DOI: 10.1111/j.1365-2265.2012.04458.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol secretory parameters in young exercisers in relation to LH secretion and bone parameters

Abstract: Objective-Amenorrhoea and low bone density are common in excessive exercisers, yet endocrine factors that differentiate adolescent amenorrhoeic exercisers (AE) from eumenorrhoeic exercisers (EE) are unclear. We have previously reported that high ghrelin and low leptin predict lower LH secretion in AE. Leptin and ghrelin impact cortisol secretion, and hypercortisolaemia can inhibit LH pulsatility. We hypothesized that higher cortisol secretion in young endurance weight-bearing AE compared with EE and non-exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 41 publications
4
39
0
2
Order By: Relevance
“…Adipocytes are responsible for the secretion of leptin and adiponectin, which, as mentioned earlier, have opposing effects on the HPG axis [89][90][91][92] . There is consistent evidence that amenorrheic athletes with normal lean body mass and BMI have lower body fat and percent body fat than eumenorrheic athletes and nonathletes [93,94] . Leptin, an anorexigenic hormone, declines with low energy availability [95,96] and, as expected, is lower in amenorrheic athletes compared to eumenorrheic athletes and nonathletes [74,93] .…”
Section: Female Athlete Triadmentioning
confidence: 95%
“…Adipocytes are responsible for the secretion of leptin and adiponectin, which, as mentioned earlier, have opposing effects on the HPG axis [89][90][91][92] . There is consistent evidence that amenorrheic athletes with normal lean body mass and BMI have lower body fat and percent body fat than eumenorrheic athletes and nonathletes [93,94] . Leptin, an anorexigenic hormone, declines with low energy availability [95,96] and, as expected, is lower in amenorrheic athletes compared to eumenorrheic athletes and nonathletes [74,93] .…”
Section: Female Athlete Triadmentioning
confidence: 95%
“…Thus severe energy depletion (as in AN) that causes severe weight loss likely has a different effect on fat distribution than less severe energy depletion where weight is preserved (as in normal-weight OAA). In a previous study, we reported that OAA have higher cortisol than EA and non-athletes [23]. Because increased cortisol favors central adiposity [24, 25], it is possible that trunk fat redistribution in OAA is at least partially mediated by increased cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Despite refutation of the exercise stress hypothesis (ie, that activation of the HPA axis solely leads to reproductive dysfunction) in favour of the energy availability hypothesis,41 the observation remains that FHA is associated with elevated central and peripheral levels of cortisol 36 56. Vulliémoz et al 57 demonstrated this in female rhesus monkeys, in whom negative energy balance and reproductive dysfunction had been induced by ghrelin infusion.…”
Section: Hypothalamic Adaptations To Exercisementioning
confidence: 99%
“…Subsequently, in a cross-sectional analysis of overnight hormone levels in adolescent amenorrhoeic endurance athletes, Ackerman et al 36 demonstrated cortisol levels were independently associated with reduced LH pulsatility after correcting for leptin, ghrelin and fat mass. These studies suggest that the action of gut peptides in the reduced energy availability state is mediated through activation of the HPA axis.…”
Section: Hypothalamic Adaptations To Exercisementioning
confidence: 99%